Die Schuldenbremse der Bundesländer: Eine Fehlkonstruktion? - Gebhard Kirchgässner (Wirtschaftsdienst, 2014)
2009 wurde in Deutschland eine Schuldenbremse für den Bundeshaushalt ab 2016 und die Länderhaushalte ab 2020 beschlossen. Sie orientiert sich am Schweizer Modell. Allerdings haben die Bundesländer in Deutschland - anders als die Schweizer Kantone - keine Steuerautonomie. Da die Länder aber dringend Investitionen tätigen müssen, bezweifelt der Autor, dass sich tatsächlich alle Länder an die Schuldenbremse halten werden. – – The debt brake for the German Länder, which forbids them from taking on new net debt beginning in 2020, has two major shortcomings. First, the Länder do not have tax autonomy. In fiscal crises, they can only adjust on the expenditure side, not on the revenue side. Given the fact that most expenditure is predetermined by law, in such a crisis, a balanced budget without new debt would hardly be feasible. Second, it is not taken into account that, in particular in small regional units, large investments can hardly be financed by current expenditure. Thus, there is a very high probability that at least some Länder will still take on new net debt after 2020 and, therefore, violate the rules of the debt brake.
Keywords: H70; H71; H74; 330; Haushaltskonsolidierung; Steuereinnahmen; Investition; Teilstaat; Deutschland